MUDRA SCHEME IN PUNJAB: AN ANALYSIS - Kaur, Kuljeet (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India has large potential for developing start-ups due to presence of hardworking, competent and skilful youth in the country. Start-ups are small enterprises/businesses started by some individual or group of individuals to materialise some of their viable business idea. But the start-up founders may face challenges like risk factors, India's inadequate infrastructure and obtaining timely and sufficient funding. The Government of India's MUDRA initiative is greatly helpful for lending money to these kinds of enterprises. Under MUDRA Scheme loan up to Rs. 10 lakh is provided to non-corporate, non-farm small/micro businesses. So main aim of this paper is to analyse progress of Mudra Scheme in Punjab by evaluating the number of accounts that have been opened under the scheme and how much loan amount has been sanctioned and dispersed over the years. Although Punjab saw a growth in the number of accounts registered under the Mudra plan throughout the period, a closer examination of the data and statistics presented in the paper and the comparative analysis of accounts opened in Punjab and national level highlight that Punjab shares a very small number of accounts opened under the scheme.